A multi-perspective view of the effects of a pipeline explosion in Nigeria - Makinde, E. O.; Eludoyin, Adebayo O; Salami, Ayobami T (International Journal of Disaster Risk Reduction, 2023)
International Journal of Disaster Risk Reduction, Issue no:2013, Pg. 68–77.